2021
DOI: 10.1108/arj-10-2020-0329
|View full text |Cite
|
Sign up to set email alerts
|

A study of the reliability of cross-sectional earnings forecasting models for estimating IPO firms’ implied cost of capital

Abstract: Purpose This study aims to evaluate the earnings forecasting models of Hou et al. (J Account Econ, 53:504–526, 2012) and Li and Mohanram (Rev Account Stud, 19:1152–1185, 2014) in terms of bias and accuracy and validity of the implied cost of capital (ICC) estimates for a sample of initial public offerings (IPOs). Design/methodology/approach The authors use a sample of 1,657 NYSE, Amex and Nasdaq IPOs from 1972 to 2013. Findings The models of Hou et al. and Li and Mohanram produce relatively inaccurate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The dearth of historical data pertaining to stock performance, firm' operations and financials and complex business models enhance the information asymmetry and ambiguity in valuing the firms (Barg et al, 2021;Gerard Sanders and Boivie, 2004;Menon and James, 2022). Studies found the traditional valuation approaches, namely, the comparable firm approach and the discounted cash flow method, inefficacious in capturing the precise estimates of new firms (Berkman et al, 2000;Bilinski and Eames, 2019;Schosser and Str€ obele, 2019;Schreder and Bilinski, 2021). Kim and Ritter (1999) observed the price-earnings, marketto-book and price-to-sales multiples without adjustment to be modestly effective in valuing young ventures (Kim and Ritter, 1999).…”
Section: Ipo Performance and Valuation Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dearth of historical data pertaining to stock performance, firm' operations and financials and complex business models enhance the information asymmetry and ambiguity in valuing the firms (Barg et al, 2021;Gerard Sanders and Boivie, 2004;Menon and James, 2022). Studies found the traditional valuation approaches, namely, the comparable firm approach and the discounted cash flow method, inefficacious in capturing the precise estimates of new firms (Berkman et al, 2000;Bilinski and Eames, 2019;Schosser and Str€ obele, 2019;Schreder and Bilinski, 2021). Kim and Ritter (1999) observed the price-earnings, marketto-book and price-to-sales multiples without adjustment to be modestly effective in valuing young ventures (Kim and Ritter, 1999).…”
Section: Ipo Performance and Valuation Anomaliesmentioning
confidence: 99%
“…Studies found the traditional valuation approaches, namely, the comparable firm approach and the discounted cash flow method, inefficacious in capturing the precise estimates of new firms (Berkman et al. , 2000; Bilinski and Eames, 2019; Schosser and Ströbele, 2019; Schreder and Bilinski, 2021). Kim and Ritter (1999) observed the price-earnings, market-to-book and price-to-sales multiples without adjustment to be modestly effective in valuing young ventures (Kim and Ritter, 1999).…”
Section: Ipo Performance and Valuation Anomaliesmentioning
confidence: 99%